1978
DOI: 10.1136/bmj.2.6146.1185
|View full text |Cite
|
Sign up to set email alerts
|

Deception among smokers.

Abstract: Summary and conclusions Subjects in two different clinical trials who had been advised to stop smoking were asked if they had done so. Some 22% of subjects (11 out of 51) in the first trial and 40% (33/82) in the second trial who said they had stopped smoking were found to have raised carboxyhaemoglobin concentrations. Deception appears to be common in people trying to stop smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(53 citation statements)
references
References 4 publications
4
48
1
Order By: Relevance
“…However, the results for the conditional symmetry model (G2 = 5.4, df= 2) were acceptable. Based upon this model for mothers having smoking cat- egories that were not in agreement (ie off the main diagonal), the probability that the self reported smoking was less than the cotinine categorisation was, on average, 5.36 times more likely than the reverse. This model provides strong evidence that mothers were systematically under-reporting the amount smoked.…”
Section: Reply Groupmentioning
confidence: 99%
“…However, the results for the conditional symmetry model (G2 = 5.4, df= 2) were acceptable. Based upon this model for mothers having smoking cat- egories that were not in agreement (ie off the main diagonal), the probability that the self reported smoking was less than the cotinine categorisation was, on average, 5.36 times more likely than the reverse. This model provides strong evidence that mothers were systematically under-reporting the amount smoked.…”
Section: Reply Groupmentioning
confidence: 99%
“…Cotinine has higher sensitivity and specificity, but carbon monoxide is more convenient to measure and is only modestly less useful.5 Having reviewed the literature using salivary cotinine as a marker for self-reported smoke exposure, Etzel found that sensitivity and specificity of the procedure, when reported, were typically well above 90%. 2 Jarvis et al compared 11 different measures of smoking on a sample of 211 hospital outpatients and found that salivary cotinine had a sensitivity of 95% and a specificity of 82%, whereas carbon monoxide had both a sensitivity and a specificity of 84%.5 In comparing either of these biochemical measures to self-report, there are assumed to be two major sources of disagreement. The first is the error in measurement of cotinine or carbon monoxide, and the second is the error in self-report.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine, carboxyhemoglobin (Sillett et al, 1978), thiocyanate (Butts et al, 1974), and carbon monoxide (Ashton et al, 1981) concentrations in blood have been used as biomarkers to quantify exposure to ETS in direct and passive smokers. Nicotine concentrations in air have been used as an indicator of ETS exposure in many studies (Rothberg et al, 1998).…”
Section: Introductionmentioning
confidence: 99%